Study of Clinical Profile and In-Hospital Outcomes of Patients Undergoing Percutaneous Transvenous Mitral Commissurotomy - Shabeer, Hassan (Biological and Clinical Sciences Research Journal, 2025)
Percutaneous Transvenous Mitral Commissurotomy (PTMC) is the preferred treatment for patients with symptomatic severe rheumatic mitral stenosis and favorable valve morphology. It replicates the physiological mechanism of surgical commissurotomy with less invasiveness. Objective: This study aimed to assess the clinical profile and in-hospital outcomes of patients undergoing PTMC at a tertiary cardiac care center. Methods: A prospective observational study was conducted at the Armed Forces Institute of Cardiology, Rawalpindi, from July 1 to December 31, 2023. A total of 96 patients with severe rheumatic mitral stenosis who met the eligibility criteria underwent PTMC. Baseline demographic, clinical, and echocardiographic data were recorded. Pre- and post-procedural mitral valve area (MVA), mean transmitral gradient, and pulmonary artery systolic pressure (PASP) were assessed. Procedural success and in-hospital complications were documented. Data were analyzed using SPSS version 26.0, with p-values <0.05 considered significant. Results: The mean age of the study population was 38.6 ± 10.4 years, with a female predominance (78.1%). Most patients (68.8%) presented in NYHA Class III. Mean MVA increased significantly from 0.89 ± 0.12 cm² to 1.85 ± 0.21 cm² (p < 0.001). Mean transmitral gradient reduced from 17.4 ± 4.3 mmHg to 6.9 ± 2.1 mmHg (p < 0.001), and PASP decreased from 58.6 ± 13.2 mmHg to 39.5 ± 9.4 mmHg (p < 0.001). Procedural success was achieved in 92.7% of patients. Mild and moderate mitral regurgitation developed in 18.8% and 4.2% of cases, respectively. Complications included cardiac tamponade (2.1%) and vascular hematoma (3.1%). There was no in-hospital mortality. Conclusion: PTMC is a safe and effective intervention for severe rheumatic mitral stenosis, resulting in significant hemodynamic and symptomatic improvement with minimal complications. Proper patient selection and procedural expertise are key to successful outcomes.